DAYA DUKUNG SUMBERDAYA AIR SEBAGAI PERTIMBANGAN PENATAAN RUANG - Asdak, Chay (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2006)
The concept of carrying capacity of water resource is applied as amanagement tool for the operationalization of sustainable regional planning.Carrying capacity of a region, comprising its supportive and assimilativecapacities, is defined as the ability to produce desired outputs from a resourcebase to achieve a higher and more equitable quality of life, while maintainingdesired environmental quality. The proposed conceptual model for thecarrying capacity-based planning process considers problems, constrainingand supporting factors, and interrelated systems within a dynamic ecosystemto arrive at the water resource-based sustainable regional planning.